Physicochemical and in-vitro biological analysis of bio-functionalized titanium samples in a protein-rich medium. (August 2019) - Rao, Shradha; Hashemi Astaneh, Sarah; Villanueva, Jose; Silva, Filipe; Takoudis, Christos; Bijukumar, Divya; Souza, Júlio C.M.; Mathew, Mathew T.
Abstract: The long-term survivability of the implants is strongly influenced by the osseointegration aspects of the metal-bone interface. In this study, biological materials such as fibrinogen and fibrin are used to functionalize titanium surfaces to enhance the ability of implants to interact with human tissues for accelerated osseointegration. The biofunctionalized samples that were assessed by White Light Microscope, Scanning Electron Microscope and Water Contact Angle for surface properties proved samples etched with HF/HNO3 to be better than HCl/H2 SO4 in terms of having optimum roughness and hydrophilicity for our further experiments. To further investigate the in vitro osseointegration of the biofunctionalized samples, Osteoblasts were cultured on the surfaces to assess cell proliferation, adhesion, gene expression as well as the mineralization process. Further bacterial adhesion ( Enterococcus faecalis) and electrochemical evaluation of surface coating stability were carried out. Results of the study show that the biofunctionalized surfaces provided high cell proliferation, adherence, gene expression, and mineralization compared to other control surfaces hence proving them to have efficient and enhanced osseointegration. Also, bacterial adhesion studies show that there is no augmented growth of bacteria on the biofunctionalized samples in comparison to control surfaces. Electrochemical studies proved the existence of a stable protein layer on the bio functionalized surfaces. Such a method can reduce the time for osseointegration that can decrease risks in early failures of implants due to its enhanced hydrophilicity and cytocompatibility.